"I can't just post anything I want": Self-management of South Korean sports stars on social media. (May 2022) - Yoo, Eunhye
This study explores the influence and sociocultural meaning of self-management of South Korean sports stars in the context of their social media activity. The study utilizes netnography to analyze social media posts to determine the meaning of sports stars' self-management. Data were collected through in-depth interviews with study participants. Ten South Korean sports stars, who are active users of Instagram, were selected as the study participants. Photographs, videos, and stories from their accounts—around 1800 posts in total—were analyzed. The results indicated that the sports stars attempted to share their daily lives on social media to build a close relationship with the public. Moreover, they used their accounts to publicize their commercialized selves and to promote their sponsors. They uploaded only strictly composed and curated posts on their accounts as a form of self-censorship. Finally, it was determined that digital labor was used for self-management on social media, where there is no distinction between public and private territory. A sports star has become a self-living commercial today, and self-management is now a prerequisite for survival. Thus, self-management on social media has become a requirement for sports stars.